Gleason Score Correlation Between Prostate Needle Biopsy and Radical Prostatectomy Materials - Neşe YELDIR; Esin YILDIZ; Gökçe DÜNDAR (Federation of Turkish Pathology Societies, 2019)
Objective: Prostate cancer is the second most common cancer in men. Digital rectal examination, transrectal ultrasonography and serum prostate specific antigen represents a diagnostic triad for the detection of prostatic carcinoma. About 50 years ago, Dr. Donald Gleason created a grading system for prostate cancer based on its histologic patterns. Currently, this system maintains its validity with various changes. New updates were made in 2005 and 2014 by the International Society of Urological Pathology. The goal of biopsies is to determine the Gleason score and prognosis in prostatectomy material. The aim of this study was to determine the concordance of the Gleason score, tumor volume and tumor laterality between prostate needle biopsy and prostatectomy materials. Material and Method: The study was performed with 112 patients who had biopsy and prostatectomy materials. The Gleason grades of the tumors have been evaluated with the new grading system. Tumor volumes were calculated by the number of positive blocks while tumor laterality was evaluated as unilateral or bilateral. Statistical analysis was performed on the obtained data. Results: Gleason score, tumor volume and tumor laterality discordance between needle biopsy and prostatectomy materials was found to be statistically significant. However, the concordance increased as the Gleason score and tumor volume increased. Conclusion: Digital examination, serum prostate specific antigen value and needle biopsy together are very sensitive for a prostate adenocarcinoma diagnosis. The Gleason score, localization and volume of the tumors are important for patient follow-up, treatment and prognosis.